ROLE-PLAYING GAME TECHNOLOGY IN THE PEDAGOGICAL PROCESS (CAHIERS MAGELLANES-NS, 2025)
The article discusses the content of role-playing games organized with children, the importance of the game as the main form of activity, the history of its origin, its types and some examples of its effective organization. The concept of role-playing games originated in the 20th century and was initially employed in psychotherapy, personal development groups, and educational contexts. These games allow participants to assume roles, simulate real-life scenarios, and experience emotions related to their roles. Such activities provide a platform for learning social norms, developing teamwork, and enhancing problem-solving abilities.The study highlights how role-playing games serve as multifunctional educational tools that support intellectual, emotional, and social growth. By engaging in these games, children acquire essential life skills, explore creative problem-solving, and gain invaluable personal experiences in a structured yet imaginative environment. The findings emphasize the importance of integrating role-playing games into the pedagogical process to nurture holistic development in students.